SARS-COV-2 influence on the general practice in North Macedonia: Viewpoints of the general population and practitioners - Viktor Denkovski; Goce Gavrilov (University American College Skopje, 2021)
During pandemic times, like the SARS-CoV-2 outbreak, the chance of spreading the virus in the community and the individual health risk of the population especially for chronic patients is imminent. The dramatic increase of Covid-19 cases and the various health measures issued by the governments as lockdowns, curfews, gathering limitations, etc. led to changes in the way of life and had a tremendous effect on the mental health of the population. Furthermore, it raised the awareness of the population concerning their health risk while visiting the physicians, which additionally had an impact on the general practice as the first line of defense. Aim: The aim of this study is to investigate the views and expectations of the population concerning some of these issues. Methodology: Questionnaires were distributed at the peak of the Coronavirus outbreak (June to August 2020) in R.N. Macedonia. One survey was emailed to 2200 individual general practitioners and one was distributed randomly via emails and social networks for the public, which included participants above 15 years of age. SPSS statistical software was used to analyze the gathered data. Findings: Findings indicate that participants showed increased concerns about their safety and health risks in comparison to the time before the pandemic when visiting the general practitioner. Additionally, the general practitioners revealed increased concerns about their own and the patients' safety in their medical facilities during the outbreak. Contribution: Governments and public health authorities should consider these findings, use them as a reference, and carefully see how all of this is influencing the population before issuing additional restrictions and regulations in which the general practice is affected during pandemics.
Keywords: 330; SARS-CoV-2; general practice; patients; general practitioner; health risks; COVID-19 case